SISTEM PENDUKUNG KEPUTUSAN PENERIMAAN MURID BARU MENGGUNAKAN METODE AHP DAN SAW - Maulana Ashari; Siti Halimatun Jannah; Sofiansyah Fadli; Saikin (STEKOM PRESS, 2021)
The decision support system as a tool for decision making, has now begun to be widely applied in various fields of life, not least in making a decision for the process of accepting new students at the MA Sabilurrasyad NW Barabaliused. With the decision support system (SPK) can help schools in the selection of new students. The method used in building a decision support system in this research is the Analytical Hierarchy Process (AHP). The method used to select new students is the Analytical Hierarchy Process (AHP) which functions to calculate the final score of each student in the school and the Simple Additive Weighting (SAW) serves to rank each student.The result of this study is that the combination of the AHP (Analytical Hierarchy Process) and SAW (Simple Additive Weighting) methods in determining new student admissions at the MA Sabilurrasyad NW Barabali School can be used. SPK (Decision Making System) can display information according to what the user inputs correctly.